Evaluation of ship performance in international maritime transportation using an onboard measurement system - in case of a bulk carrier in international voyages. (1st August 2015) - Sasa, Kenji; Terada, Daisuke; Shiotani, Shigeaki; Wakabayashi, Nobukazu; Ikebuchi, Takuro; Chen, Chen; Takayama, Atsuyoshi; Uchida, Makoto
Abstract: The present global society has made the development of a safe and efficient maritime transportation system more imperative than ever before. Of particular impetus is the steep rise in the price of crude oil, which has required shipping companies to minimize the fuel consumption of their ships. Moreover, the emission of carbon dioxide has been restricted by the EEDI (Energy Efficiency Design Index) issued by the IMO (International Maritime Organization). Weather routing services have become more important to shipping companies. However, there are accuracy deficiencies in the numerical models employed by such services for purposes such as weather forecast and the ship speed loss phenomenon. Moreover, the development of weather routing models has been hampered by insufficient accumulation of continuous data on ship motions, and the navigation, engine, and weather parameters. The data used for this study was collected over one year from a 20, 000 DWT class bulk carrier on worldwide voyages. Some new relationships regarding ship motions, speed loss, and wave conditions were developed, which were verified by experimental data and numerical simulations of the frequency response of the ship motion and of the weather and ocean. Highlights: Various parameters are analyzed to evaluate the ship behavior in heavy seas. Wave information is validated by the comparison between measurement and simulation. Estimation of ship motions can be shown in follow and head seas in actual seas. The speed loss should be estimated by ship motions, rather than wave height. Simple estimation models on speed loss and fuel consumption are newly introduced.